2020
DOI: 10.3390/app10093185
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of Integrated Model of Quarter Car Semi-Active Seat Suspension with Human Model

Abstract: In this paper, an integrated model of a semi-active seat suspension with a human model over a quarter is presented. The proposed eight-degrees of freedom (8-DOF) integrated model consists of 2-DOF for the quarter car model, 2-DOF for the semi-active seat suspension and 4-DOF for the human model. A magneto-rheological (MR) damper is implemented for the seat suspension. The fuzzy logic-based self-tuning (FLST) proportional–integral–derivative (PID) controller allows to regulate the controlled force on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In [10], a 8-DOF integrated model of a semi-active seat suspension with a human model over a quarter is presented. A fuzzy logic-based self-tuning PID controller allows to regulate the controlled force on the basis of sprung mass velocity error and its derivative as input.…”
Section: Modelling and Control Of Mechatronic And Robotic Systemsmentioning
confidence: 99%
“…In [10], a 8-DOF integrated model of a semi-active seat suspension with a human model over a quarter is presented. A fuzzy logic-based self-tuning PID controller allows to regulate the controlled force on the basis of sprung mass velocity error and its derivative as input.…”
Section: Modelling and Control Of Mechatronic And Robotic Systemsmentioning
confidence: 99%
“…To improve ride comfort, the vehicle's suspension systems were researched and controlled based on advanced control approaches. [1][2][3][4][5][6] The results showed that the vehicle's ride comfort was significantly reduced. However, with the soil compactors and heavy trucks, the comfort in these vehicles is still low.…”
Section: Introductionmentioning
confidence: 99%
“…Active suspension is a system that adds an active controller, which actively generates the corresponding damping force according to different external disturbances as a way to adjust the movement of the body. e practical application of active suspension in vehicles is limited due to its higher power consumption and lower reliability [5]. Semiactive suspension is widely used, which does not require high power semiactive suspension, while it adjusts the damping characteristics by means of low power signals.…”
Section: Introductionmentioning
confidence: 99%